Kradzież patentów jako element strategii konfliktu państw autorytarnych – casus Rosji - Niklewicz-Pijaczyńska, Małgorzata (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
The article refers to the problem of infringement of intellectual property rights, in particular patent rights, as an element of the conflict strategy implemented by the Russian Federation. Legally sanctioned patent theft is a deliberate and carefully planned activity. It represents the first step on the road to further appropriation of the intellectual property of countries considered hostile. For international justification, the Russian government invokes the need to close the deepening economic gap created by the withdrawal of European and American companies and the coexisting deficit of goods and services. However, the introduction of solutions that allow for penalty-free and unlimited imitation of protected solutions leads to a situation in which the Russian Federation is not only squeezed out of the global technology market, but also wipes out its own innovative activity based on original inventions. In its approach, the Russian side does not take into account the well-known economic regularity — while a military conflict can stimulate economic mechanisms in the short term, a technological conflict prevents development in the long term. The main objective of the article is to present the evolution of the Russian Federation’s patent strategy as a result of the ongoing military conflict in the context of the applied negotiation tactics. An additional objective is to try to estimate future global technological position changes of the conflicting parties. For this purpose, the following stages of changes in Russian patent law were studied and empirical data on patent activities of domestic companies were analysed. The conclusions of the analysis indicate that the consequences of the potentially massive application of the decree are far-reaching for each of the parties to the conflict. At the same time, the use of tactics characteristic for the hard negotiation style, in which the win of one side means the loss of the other side, leads to a stalemate situation in which none of the parties to the ongoing conflict is strong enough to break the impasse and establish the rules of the game in accordance with the legal order and market rules. Such a situation, in which the parties become hostages in the decision-making process, i.e. the prisoner’s dilemma, is known from the economic history of the Cold War period. However, while at that time its context was primarily of a military nature, today it takes place on a technological level, determining the future of the conflicting economies.
Keywords: patenty; innowacje; własność intelektualna